Використання онтологічних моделей в цифровізації транспорту: проблеми та перспективи (Transport systems and technologies, 2020)
The article deals with current problems and prospects of digitalization of transport (transport systems). It is suggested to use modeling of processes and objects of transport systems to solve the problems under consideration. Ontology models are considered as models used for the digitization of transport. The article deals with the problems and prospects of using ontologies in the digitization of transport (transport systems, in particular rail systems and its infrastructure: buildings, bridges, etc.). To solve the problems of digitization of transport, ontologies, formalized ontological and semantic languages ​​are essential for ensuring the design and operation of transport systems. Ontological models embrace the processes that take place in transport and play an increasingly crucial role. The article discusses, in particular, how ontological models can provide and visualize detailed information about commands (control messages) exchanged by subsystems of transport systems. The article examines the global experience in digitalisation of transport based on the use of formal ontological models, describes ontologies built on SysML, which are common in transport security systems (in particular, for various types of rail signaling systems).
Keywords: digital economy, transport digitalization, semantic models, ontological models, engineering ontologies